RECONSTRUCCIÓN MAMARIA CON COLGAJO DE PERFORANTES DE LA ARTERIA EPIGÁSTRICA INFERIOR. UTILIDAD DE LA ANGIO TOMOGRAFÍA COMPUTADA MULTIDETECTOR EN LA PLANIFICACIÓN PREQUIRÚRGICA (Revista Argentina de Cirugía, 2022)
Objetive: Is to establish the utility of the Angiographic Multidetector Computed Tomography (AngioTCMD) as the image modality of choice in the presurgical evaluation of mastectomized patients who will undergo to a deep inferior epi- gastric perforator (DIEP) flap breast reconstruction.Population: Between April 2008 and March 2011, eleven patients who underwent an autologous flap breast recons- truction, were evaluated.Method: The study is aimed to localize the perforating artery supplying the flap to be used for breast reconstruc- tion.The data provided by the AngioTCMD were correlated with the Doppler ultrasound (U.S.) intraoperatively and the surgical dissection findings.Conclusion: The AngioTCMD with three-dimensional reconstruction was highly effective in the election and location of the highest caliber perforating arteries and lower intramuscular route, using as a reference method of surgical dis- section. Thus makes the method, an excellent pre surgical study for the planning of this reconstruction technic, giving the surgical team a significant reduction in surgery's time, decreasing the intra and postoperative morbimortality.
Keywords: perforator flap; DIEP; angioTCMD